Redetermination of 2,2′-bipyridine-1,1′-diium dibromide - Ali, Basem F. (International Union of Crystallography, 2012)
In the title molecular salt, C(10)H(10)N(2) (2+)·2Br(−), the dihedral angle between the aromatic rings is 20.83 (14)° and the N—H groups have a transoid conformaton [N—C—C—N = 158.5 (3)°]. In the crystal, the cations are linked to the anions by two N—H⋯Br and five C—H⋯Br hydrogen bonds, generating corrugated sheets incorporating R (2) (1)(7), R (4) (2)(10), R (4) (2)(11) and two different R (4) (2)(12) loops. This structure was originally reported by Nakatsu et al. [Acta Cryst (1972), A28, S24], but no atomic coordinates are available.